Study of Thymus and T- cell Development and Tumor Immunology - Sareh Sangy; Fatemeh Alsadat Miryousefi Ata; Faegheh Miryousefiata (Budapest International Research and Critics University, 2021)
Monoclonal antibodies have proven to be effective therapeutic agents for a wide range of human cancers. However, unlike other modes of antibody action, the capacity of antibodies to activate tumor antigen-specific immune responses has received less attention. The rationale and evidence for generating anti-cancer antibodies that can induce host tumor antigen-specific immune responses are described in this paper. This can be performed by stimulating the idiotypic network, generating antibody-dependent cellular cytotoxicity, or boosting antibody-targeted cross-presentation of tumor antigens. To improve the clinical benefits of antibody therapy for human cancer, future therapeutic modifications or combinations should be able to extend, magnify, and shape these immune responses.